The possibility of using permanent magnets without rare earth elements in electric motors - A. A. Маiorov; A. R. Safin (Известия высших учебных заведений: Проблемы энергетики)
THE PURPOSE. The use of rare earth permanent magnets in electric motors has become commonplace. The use of rare earth magnets in electric motors, such as neodymium (NdFeB), gives a significant increase in the characteristics of the electric motor. The prices of permanent magnet motors made of rare earth elements are highly dependent on the prices of magnets. So in 2012, prices for rare earth magnets increased sharply, which in turn led to a sharp increase in the cost of electric motors. The difficult situation in the world, as well as a possible new price hike for rare earth magnets, is worrying. Therefore, alternatives to rare earth permanent magnets should be considered. The aim of the study is to study and compare various alternatives to rare earth permanent magnets. Compare different types of electric motors. METHODS. When solving the tasks set, a comparative analysis of magnets made of various materials was carried out, which could replace neodymium magnets, which are most often used in electric motors. A comparison of different types of electric motors was also made. RESULTS. The article describes the relevance of the topic under consideration. The problems associated with the use of rare earth magnets are considered. Alternative options for rare-earth magnets, which are used in electric motors, are considered. Various types of electric motors are considered, the pros and cons of various types of electric motors are given. CONCLUSION. The article describes the reasons why it is necessary to abandon the use of rare earth magnets in electric motors (the most common neodymium magnets). The negative aspects of the use of rare earth magnets in electric motors are described. Alternative applications of rare-earth magnets in electric motors are described. This describes the possibility of restoring rare earth magnets, as well as the possibility of using various materials to create permanent magnets. After studying the problems with the use of rare earth magnets in electric motors, they came to the conclusion that it is necessary to consider various options for electric motors that would use magnets without the use of rare earth elements. Or consider different types of electric motors that do not use permanent magnets. So to replace the widely used neodymium magnets, ferrite magnets can come.